Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I'll just show you my work and you can tell me where I career off the road and burst into flames.


set $b=u+v$ and $c=uv$, and rewrite


$y''+ uy' + vy' + (uv)y=p(x)$

$(y'' + uy') + v(y' + uy) = p(x)$

$\frac{d}{dx}(y'+uy) + v(y' + uy) = p(x)$

set $z=y'+uy$, and rewrite

$\frac{dz}{dx} + vz = p(x)$

Solve this 1st-order DE for $z$

($e^{vx}z)' = e^{vx}p(x)$

$e^{vx}z = \int e^{vx}p(x) dx + C_0$

$z = e^{-vx}\int e^{vx}p(x) dx + C_0e^{-vx}$

Sub. this back into the 1st-order DE

$y'+uy = e^{-vx}\int e^{vx}p(x) dx + C_0e^{-vx}$

Solve this 1st-order DE for $y$:

$(e^{ux}y)' = e^{ux}e^{-vx}\int e^{vx}p(x) dx + C_0e^{-vx}e^{ux}$

$(e^{ux}y)' = e^{(u-v)x}\int e^{vx}p(x) dx + C_0e^{(u-v)x}$

$e^{ux}y = \int \left[ e^{(u-v)x}\int e^{vx}p(x) dx + C_0e^{(u-v)x} \right] dx$

$e^{ux}y = \int \left[ e^{(u-v)x}\int e^{vx}p(x) dx \right] dx + C_0\int e^{(u-v)x} dx$

$e^{ux}y = \int \left[ e^{(u-v)x}\int e^{vx}p(x) dx \right] dx + \frac{C_0}{u-v}e^{(u-v)x} + C_1$

$y = e^{-ux}\int \left[ e^{(u-v)x}\int e^{vx}p(x) dx \right] dx + e^{-ux}\frac{C_0}{u-v}e^{(u-v)x} + C_1e^{-ux}$

$y = e^{-ux}\int \left[ e^{(u-v)x}\int e^{vx}p(x) dx \right] dx + e^{-vx}\frac{C_0}{u-v} + C_1e^{-ux}$

Okay, two questions: is this correct and can I simplify any further?

share|cite|improve this question
up vote 1 down vote accepted

Note that if you write $$y'' + by' + cy = p(x) = y'' -(u_0 + v_0)y' + u_0 v_0 y,$$ then $u_0$ and $v_0$ are the roots of $x^2 + bx + c = 0.$ To make things easier, your $u$ equals $-u_0$ and your $v$ equals $-v_0$. Then your expression in terms of $p(x)$, $u_0$ and $v_0$ reads $$y = e^{u_0 x}\int \left[ e^{(v_0-u_0)x}\int e^{-v_0 x}p(x) dx + C_0e^{(v_0 - u_0)x} \, \mathrm dx \right] \, \mathrm dx.$$ I'll leave it there so, when we get special cases like $u_0 = v_0$ we do not run into undefined terms.

Ultimate exercise: what happens when $$y'' + p(x)y' + q(x)y = r(x)?$$

share|cite|improve this answer
Already been down this road before. :) – Mike Oct 14 '12 at 22:07
What I have thought is a generalization of what OP was doing. Nice question! – Ian Mateus Oct 14 '12 at 22:14
btw, Now I have to solve your ultimate exercise ;) – Korgan Rivera Oct 14 '12 at 22:21
@IanMateus It now makes sense to me to consider $u_o$ and $v_0$ as roots of a quadratic. – Korgan Rivera Oct 14 '12 at 22:34
@IanMateus btw, your 'ultimate exercise' is evil and should be killed with fire. – Korgan Rivera Oct 15 '12 at 5:26

Looks about right, except for the case where $u=v$. You might be able to clean it up a bit. For starters, $C_0$ has no real significance, so you can declare a new constant $C_2=\frac {C_0}{u-v}$. That really messy part is your particular solution.

Not sure if it will work, but maybe integration by parts can clean it up a bit.

$$r=\int e^{vx}p(x)dx,dr=e^{vx}p(x)dx$$


$$y=\frac{e^{-ux}e^{(u-v)x}}{u-v}\int e^{vx}p(x)dx-\frac{e^{-ux}}{u-v}\int e^{(u-v)x}e^{vx}p(x)dx+C_2e^{-vx}+C_1e^{-ux}$$

$$y=\frac{e^{-vx}}{u-v}\int e^{vx}p(x)dx-\frac{e^{-ux}}{u-v}\int e^{ux}p(x)dx+C_1e^{-ux}+C_2e^{-vx}$$

Again, if $u=v$, that changes the homogenous solution slightly as

$$\int e^{(u-v)x}dx=\int dx=x$$

I'll leave it to someone else to explain whether or not this would work when $u$ and $v$ are complex as that's not my area of expertise.

share|cite|improve this answer
It works for all cases. When $u$ and $v$ are complex you'll just have to use $e^{i\theta}=\cos\theta +i\cdot\sin\theta$ to get further simplifications. However, when $u=v$, you cannot integrate $\int e^{(u−v)t}\, \mathrm dt$ as as usual; you will find $C_0 t + C_1$ instead. – Ian Mateus Oct 14 '12 at 21:54
@IanMateus Already mentioned that case. $\int C_0e^{(u-v)x}dx=\int C_0e^{0x}dx=\int C_0dx=C_0x+C_1$. Which when multiplied by $e^{-ux}$ results in $C_0xe^{-ux}+C_1e^{-ux}$ which is indeed what happens with a double root. – Mike Oct 14 '12 at 21:56
@KorganRivera No, $e^{0x}=e^0=1$ – Mike Oct 14 '12 at 23:09
@Mike \facepalm. Why did I even say that. -_- – Korgan Rivera Oct 14 '12 at 23:12

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.